The Influence of Using Describe And Identify Game Towards Students’ Speaking Ability at the Second Semester of Tenth Grade of SMA YP UNILA Bandar Lampung in the Academic Year of 2014/2015 - Kurniawati, Dewi; Fitria, Yeni (English Education: Jurnal Tadris Bahasa Inggris, 2017)
The research aims at investigating the influence of using describe and identify game toward students’ Speaking Ability. The students’ speaking ability at the tenth grade of SMA YP UNILA Bandar Lampung is still low. The writer applied quasi experimental design. The population of this research was the tenth grade of SMA YP UNILA Bandar Lampung. There were twelve classes of 424 students. The writer took the sample by using cluster random sampling technique, the sample were X MIA 4 as experimental class and X MIA 6 as control class. The writer conducted five meetings for each class consisting of one pre-test, three treatments and one post-test. In experimental class the writer used describe and identify game, whereas in control class the writer used dialogue memorization technique. In collecting the data, the writer used the instrument in the form of oral test. The instruments were pre-test and post-test, after giving the post-test, the writer, then, analyzed the data using independent sample ttest formula. After doing the hypothetical test, it was obtained the result of ttest was 8.7454 and the result of tcritical with the level of significance 0.05 was 2.00. The criteria to know the hypothesis is accepted or not, was tobserve higher than tcritical (tobserve > tcritical). From this statement, it is clear that 8.7454 is higher than 2.00. This result means that there is a significant influence of using describe and identify game towards students’ speaking ability at the tenth grade of SMA YP UNILA Bandar Lampung.